Reconstructions revived: A handweaver’s personal perspective - Nørgård, Anna (Archaeological Textiles Review, 2021)
Reconstructing ancient clothing has a long tradition in Scandinavian archaeology and during her professional career as a hand weaver, Anna Nørgård has produced many items of prehistoric clothing and sails for various museums in Denmark and abroad. For her, a reconstruction is a tool, a way to gather new knowledge. Nevertheless, only on rare occasions has she been asked to produce a report and document her work. This implies that most museums are not aware of the scientific potential that the reconstruction process itself offers. In this article, she shares some of her thoughts and experiences with Scandinavian Iron Age textile technology gathered while working on reconstructions of finds such as the Lønne Hede and Huldremose clothing, the Skærsø textile and multiple metres of sail cloth.